Strategi Pemasaran Dan Pengembangan Sumber Daya Manusia Sebagai Upaya Meningkatkan Kuantitas Penjualan Pada Usaha Mikro Kecil Dan Menengah (UMKM) - Asdi Asdi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine and analyze marketing strategies and human resource development as an effort to increase sales quantity in Micro, Small and Medium Enterprises (MSMEs). The approach to this research is a qualitative approach, namely data collection techniques through observation and interviews with informant sources of MSME actors. The research method used for analysis is SWOT which consists of strengths and weaknesses as internal factors, and opportunities and threats. The results of this research show that the marketing strategy carried out by MSMEs is improving product quality, market segmentation, social media and collaborating with influencers or celebrities/content creators. Meanwhile, the HR development strategy carried out by MSMEs is training and improving skills, motivation and providing incentives, leadership development. Based on the SWOT analysis, the strengths of MSMEs are authentic taste and a source of innovative ideas, while the opportunities for MSMEs are trends and development of new products and services Keywords: Marketing, Human Resources, Sales and MSMEs